Viral Infection in the Development and Progression of Pediatric Acute Respiratory Distress Syndrome - Nye, Steven; Whitley, Richard J.; Kong, Michele (Frontiers in Pediatrics, 2016)
Viral infections are an important cause of pediatric Acute Respiratory Distress Syndrome (ARDS). Numerous viruses, including respiratory syncytial virus (RSV) and influenza A (H1N1) virus, have been implicated in the progression of pneumonia to ARDS; yet the incidence of progression is unknown. Despite acute and chronic morbidity associated with respiratory viral infections, particularly in ‘at risk’ populations, treatment options are limited. Thus, with few exceptions, care is symptomatic. In addition, mortality rates for viral related ARDS have yet to be determined. This review outlines what is known about ARDS secondary to viral infections including the epidemiology, the pathophysiology and diagnosis. In addition, emerging treatment options to prevent infection, and to decrease disease burden will be outlined. We focused on RSV and influenza A (H1N1) viral-induced ARDS, as these are the most common viruses leading to pediatric ARDS, and have specific prophylactic and definitive treatment options.